Valorization of Tomato Seed By-Products as a Source of Fatty Acids and Bioactive Compounds by Using Advanced Extraction Techniques - Ignacio Solaberrieta; Ana Cristina Mellinas; Jérémy Espagnol; Mahmoud Hamzaoui; Alfonso Jiménez; María Carmen Garrigós (Foods, 2022)
In this work, lipids and bioactive compounds from tomato seed by-products were extracted and compared by using advanced extraction techniques, such as microwave-assisted extraction (MAE) and supercritical fluid extraction (SFE). The influence of different extraction parameters, including extraction temperature (T), time (t) and solvent volume (V) for MAE as well as extraction temperature (T), pressure (P) and flow rate (F) for SFE-CO2, was evaluated on tomato seed oil (TSO) yield and fatty acids composition using response surface methodology (RSM). Optimum extraction conditions for MAE were 56.2 °C, 29.0 min, and 67.6 mL, whereas conditions of 60.2 °C, 400.0 bar, and 64.6 g min−1 were found for SFE-CO2. Under these conditions, higher TSO extraction yields were obtained by MAE compared to SFE-CO2 (25.3 wt% and 16.9 wt%, respectively), while similar fatty acids profiles were found by GC in terms of FAMEs composition: methyl palmitate, methyl stearate, methyl oleate, and methyl linoleate, accounting for around 80 wt% of unsaturated fatty acids. TSO MAE extracts showed high DPPH• radical scavenging activity which was related to the presence of tocopherols; in particular γ-tocopherol, which was found as the dominant homologue (260.3 ± 0.6 mg kgTS−1) followed by a lower amount of α-tocopherol (6.53 ± 0.12 mg kgTS−1) by HPLC-DAD. The obtained results suggested that tomato seeds are an interesting source of bioactive compounds with potential use in a wide range of nutritional and food applications, increasing the added value of this by-product, which is currently underexploited.